variants are associated with multiple congenital anomalies including ciliopathy phenotypes. - Marquez, Jonathan; Mann, Nina; Arana, Kathya; Deniz, Engin; Ji, Weizhen; Konstantino, Monica; Mis, Emily K; Deshpande, Charu; Jeffries, Lauren; McGlynn, Julie; Hugo, Hannah; Widmeier, Eugen; et al. (J Med Genet, 2020)
BACKGROUND: Cilia are dynamic cellular extensions that generate and sense signals to orchestrate proper development and tissue homeostasis. They rely on the underlying polarisation of cells to participate in signalling. Cilia dysfunction is a well-known cause of several diseases that affect multiple organ systems including the kidneys, brain, heart, respiratory tract, skeleton and retina. METHODS: Among individuals from four unrelated families, we identified variants in ( that manifested in a variety of pathologies. In our proband, we also examined patient tissues. We depleted in frog embryos to generate a loss-of-function model. Finally, we tested the pathogenicity of patient variants through rescue experiments in the frog model. RESULTS: Patients with variants of were found to have a variety of phenotypes including cystic kidneys, nephrotic syndrome, hydrocephalus, limb abnormalities, congenital heart disease and craniofacial malformations. We also observed a loss of cilia in cystic kidney tissue of our proband. Knockdown of in embryos recapitulated many of these phenotypes and resulted in a loss of cilia in multiple tissues. Unlike introduction of wildtype in frog embryos depleted of introduction of patient variants was largely ineffective in restoring proper ciliation and tissue morphology in the kidney and brain suggesting that the variants were indeed detrimental to function. CONCLUSION: These findings in both patient tissues and shed light on how mutations in may lead to tissue-specific manifestations of disease. DLG5 is essential for cilia and many of the patient phenotypes are in the ciliopathy spectrum.